Application of a Fiber Optic-Based SHM System to a Composite Aircraft Wing and Its Technological Maturity Evaluation - Gianvito Apuleo; Monica Ciminello; Lorenzo Pellone; Umberto Mercurio; Antonio Concilio (EASN 2024, 2025)
This paper deals with the application of a novel fiber optic SHM system for bonding lines monitoring of a composite aircraft wing within Clean Sky 2 program framework. With the aim of controlling the structural state of the reference component, several targets may be addressed, including safety increase through a periodic update of the integrity level, maintenance costs reduction, for instance, by moving to an on-demand from the usual scheduled approach, and even design benefits by envisaging the possibility of modulating the safety coefficients due to an increased knowledge of the intimate structural system behavior. Specifically, an original SHM architecture is herein presented, based on the use of distributed optical fibers, and implementing a proprietary algorithm, to detect bonding lines damage. Ground testing with a full-scale wing box successfully validated the system’s capability to identify damage. To assess maturity, a TRL evaluation has been carried out, whose results are summarized and discussed. Such a process allowed us to highlight specific areas for technological improvement, such as modeling-testing synergy and operational environment definition. The work herein reported is expected to address these aspects while achieving full-scale aircraft integration, paving the way for enhanced structural robustness and operational safety in future aircraft.